2000
DOI: 10.1111/j.1749-6632.2000.tb05477.x
|View full text |Cite
|
Sign up to set email alerts
|

Genital Tract Infections and Perinatal Transmission of HIV

Abstract: In areas of the world where genital tract infections (GTIs) are common, the prevalence of HIV and the rate of mother‐to‐child transmission (MTCT) of HIV are also high. Although observational studies suggested that GTIs are associated with MTCT of HIV, no controlled clinical trial has confirmed this finding. It is likely that GTIs that cause either discharges or ulcers during pregnancy increase perinatal transmission of HIV. Several potential biological mechanisms might facilitate perinatal transmission. For ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 71 publications
0
43
0
Order By: Relevance
“…Observational studies from Africa suggested a strong association between chorioamnionitis and MTCTof HIV-1, e.g. odds ratio (OR) of 3.9 in a study from Kenya [2], and between BV during pregnancy and MTCTof HIV-1, OR 2.3 in a study from Malawi [4]. BV is very common among African women, with a prevalence of approximately 50% [5,6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Observational studies from Africa suggested a strong association between chorioamnionitis and MTCTof HIV-1, e.g. odds ratio (OR) of 3.9 in a study from Kenya [2], and between BV during pregnancy and MTCTof HIV-1, OR 2.3 in a study from Malawi [4]. BV is very common among African women, with a prevalence of approximately 50% [5,6].…”
Section: Introductionmentioning
confidence: 97%
“…Chorioamnionitis, inflammation of the fetal membranes, and bacterial vaginosis (BV), a disturbance in the normal vaginal ecosystem, have been associated with an increased risk of mother-to-child transmission (MTCT) of HIV-1 [1][2][3][4]. Observational studies from Africa suggested a strong association between chorioamnionitis and MTCTof HIV-1, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Apart from this STI/RTI have been shown to facilitate transmission of HIV. 5,6 Many STIs and RTIs are transmitted to the neonate by vertical transmission, thus exposing the newborn to these dreadful diseases even before birth.…”
Section: Introductionmentioning
confidence: 99%
“…25 HIV transmission is exacerbated by underlying conditions and co-infections that stimulate inflammatory responses in tissues. [26][27][28] Strains of probiotic breastmilk bacteria with both antiviral activity and proven anti-inflammatory effects may therefore be considered advantageous for application in breastfeeding infants exposed to HIV to reduce the risk of virus transmission. 29 While promising in concept, further studies are needed to fully elucidate the mechanism(s) by which breastmilk LAB inhibit the infectivity of HIV-1, by both bacterial cells and soluble microbial products, and to identify those LAB strains with the most significant potential for development as probiotics.…”
Section: Discussionmentioning
confidence: 99%